Nerve growth factor facilitates perivascular innervation in neovasculatures of mice - Mitsuhiro Goda; Shingo Takatori; Saori Atagi; Narumi Hashikawa-Hobara; Hiromu Kawasaki (Elsevier, 2016)
It is well known that blood vessels including arterioles have a perivascular innervation. It is also widely accepted that perivascular nerves maintain vascular tone and regulate blood flow. Although there are currently prevailing opinions, unified views on the innervation of microcirculation in any organs have not been established. The present study was designed to investigate whether there are perivascular nerves innervated in microvessels and neovessels. Furthermore, we examined whether nerve growth factor (NGF) can exert a promotional effect on perivascular nerve innervation in neovessels of Matrigel plugs. A Matrigel was subcutaneously implanted in mouse. The presence of perivascular nerves in Matrigel on Day 7-21 after the implantation was immunohistochemically studied. NGF or saline was subcutaneously administered by an osmotic mini-pump for a period of 3-14 days. The immunostaining of neovasculatures in Matrigel showed the presence of perivascular nerves on Day 21 after Matrigel injection. Perivascular nerve innervation of neovessels within Matrigel implanted in NGF-treated mice was observed in Day 17 after Matrigel implantation. However, NGF treatment did not increase numbers of neovessels in Matrigel. These results suggest that perivascular nerves innervate neovessels as neovasculatures mature and that NGF accelerates the innervation of perivascular nerves in neovessels.